2019
DOI: 10.1155/2019/3857853
|View full text |Cite
|
Sign up to set email alerts
|

An Oncogenic Role for Four-Jointed Box 1 (FJX1) in Nasopharyngeal Carcinoma

Abstract: Nasopharyngeal carcinoma (NPC) is a highly metastatic cancer prevalent in Southern China and Southeast Asia. The current knowledge on the molecular pathogenesis of NPC is still inadequate to improve disease management. Using gene expression microarrays, we have identified the four-jointed box 1 (FJX1) gene to be upregulated in primary NPC tissues relative to nonmalignant tissues. An orthologue of human FJX1, the four-jointed (fj) gene in Drosophila and Fjx1 in mouse, has reported to be associated with cancer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
0
10
0
1
Order By: Relevance
“…18 Although the exact biological function of FJX1 in human cancers remains unclear, studies of different species indicate that FJX1 participates in carcinogenesis and FJX1 gene amplification as well as subsequent mRNA expression have been found, besides, FJX1 has also been considered as a candidate for regulation of angiogenesis in several human cancers, including CRC. [19][20][21] However, whether specific crosstalk existed between PVT1 and FJX1 through competition for miR-106b-5p binding in CRC is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…18 Although the exact biological function of FJX1 in human cancers remains unclear, studies of different species indicate that FJX1 participates in carcinogenesis and FJX1 gene amplification as well as subsequent mRNA expression have been found, besides, FJX1 has also been considered as a candidate for regulation of angiogenesis in several human cancers, including CRC. [19][20][21] However, whether specific crosstalk existed between PVT1 and FJX1 through competition for miR-106b-5p binding in CRC is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Microarrays and WES have facilitated the identification of several candidate biomarkers such as FJX, WNT5A, CLDN1, FGFR3, FZD6, and SOX4. Among these genes, it was reported that the four-jointed box 1 (FJX1) is overexpressed in NPC tissues and promotes cell proliferation through regulating Cycline D1 and E1 [ 32 ]. Furthermore, several key signaling pathways such as Notch, NF- κ B, and PI3K/Akt were frequently altered during NPC development and progression [ 26 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…As alluded to in the introduction, the study of extracellular kinases was spearheaded by Ken Irvine’s laboratory when they published the first example of a secreted kinase, the fly protein Fj, which they went on to show phosphorylated unusual cadherin domains ( 12 ). The murine equivalent of Fj, four-jointed box 1 (FJX1) is involved in forming appropriate dendrite arbor morphology in the hippocampus ( 24 ), and recently, human FJX1 has been shown to increase the invasive potential of nasopharyngeal cancer cells ( 25 , 26 ). In addition to FJX1 and Fam20A, B, and C, this small family contains two additional members, Fam198A and Fam198B.…”
Section: Secreted Kinasesmentioning
confidence: 99%